The Effect of Eliminating Intermediate Severity Drug-Drug Interaction Alerts on Overall Medication Alert Burden and Acceptance Rate - Knight, Amy M.; Maygers, Joyce; Foltz, Kimberly A.; John, Isha S.; Yeh, Hsin Chieh; Brotman, Daniel J. (Applied Clinical Informatics, 2019)
Objective This study aimed to determine the effects of reducing the number of drug-drug interaction (DDI) alerts in an order entry system.Methods Retrospective pre–post analysis at an urban medical center of the rates of medication alerts and alert acceptance during a 5-month period before and 5-month period after the threshold for firing DDI alerts was changed from “intermediate” to “severe.” To ensure that we could determine varying response to each alert type, we took an in-depth look at orders generating single alerts.Results Before the intervention, 241,915 medication orders were placed, of which 25.6% generated one or more medication alerts; 5.3% of the alerts were accepted. During the postintervention period, 245,757 medication orders were placed of which 16.0% generated one or more medication alerts, a 37.5% relative decrease in alert rate (95% confidence interval [CI]: −38.4 to −36.8%), but only a 9.6% absolute decrease (95% CI: −9.4 to −9.9%). 7.4% of orders generating alerts were accepted postintervention, a 39.6% relative increase in acceptance rate (95% CI: 33.2–47.2%), but only a 2.1% absolute increase (95% CI: 1.8–2.4%). When only orders generating a single medication alert were considered, there was a 69.1% relative decrease in the number of orders generating DDI alerts, and an 85.7% relative increase in the acceptance rate (95% CI: 58.6–126.2%), though only a 1.8% absolute increase (95% CI: 1.3–2.3%).Conclusion Eliminating intermediate severity DDI alerts resulted in a statistically significant decrease in alert burden and increase in the rate of medication alert acceptance, but alert acceptance remained low overall.
Keywords: clinical decision support; medication alerts; high-alert medications; computerized physician order entry; alert fatigue